TABARUKAN DI KALANGAN KHOTIMIN KHOTIMAT 30 JUZ - Maelina, Elsi (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Tabarukan is the activity of a person who expects a better life by doing a certain activity.This study used the living Qur'an method to examine the perception of khotimin khotimat 30 JUZ towards tabarukan. The wisdom of this study is to provide information that the tabarukan tradition is a tradition inherited from the previous khotimin khotimat that is preserved to the present day. Tabarukan is mandatory and not mandatory, as for students who have memorized and have not done tabarukan but have a desire to live the tradition, because they want to get barokah and to strengthen and facilitate memorization. In addition, there are also islamic boarding schools that do not have the tabarukan tradition and do not require their students to tabarukan.